On a conjecture of R. Brück concerning meromorphic function sharing small functions - Yan Xu, Hong (2017)
In this paper, we investigate the uniqueness problem on a conjecture of R. Brück concerning meromorphic function sharing the set of small functions with its derivative, and obtain some results which improve the theorems given by Zhang and Yang.